Genome-Wide Introgression and Quantitative Trait Locus Mapping Reveals the Potential of Asian Cotton (Gossypium arboreum) in Improving Upland Cotton (Gossypium hirsutum) - Feng, Liuchun; Chen, Yu; Xu, Min; Yang, Ying; Yue, Haoran; Su, Qiao; Zhou, Chenhui; Feng, Guoli; Ai, Nijiang; Wang, Ningshan; Zhou, Baoliang (Frontiers in Plant Science, 2021)
Gossypium arboreum (2n=2x=26, A2), the putative progenitor of At-subgenome of G. hirsutum (2n=4x=52, AD), is a repository of genes of interesting eliminated during evolution/domestication of G. hirsutum. However, its valuable genes are still untapped so far due to the species isolation. Here, using a synthetic amphiploid (AADDA2A2) previously reported, we developed a set of 289 G. arboreum chromosome segment introgression lines (ILs) in G. hirsutum by expanding the backcrossing population and precisely marker-assisted selection although complex chromosomal structure variations existed between parents severely hinder introgression. Our results showed the total coverage length of introgressed segments was 1116.29 Mb, representing 78.48% of the At-subgenome in G. hirsutum background, with an average segment-length of 8.69 Mb. A total of 81 co-QTLs for yield and fibre quality were identified by both RSTEP-ADD-based QTL mapping and GWAS analysis, with 1.01–24.78% of the phenotypic variance explained. Most QTLs for boll traits showed negative, but G. arboreum still has the potential to improve boll-number traits in G. hirsutum. Most QTLs for fibre quality showed negative, implying these QTLs were domesticated in G. hirsutum compared with G. arboreum and, a small quantity of fibre-quality QTLs showing positive conversely, however, indicates that G. arboreum has the underlying genes of enhancing fibre quality of G. hirsutum. This study provides new insights into the breeding genetic potential of G. arboreum, lays the foundation for further mining favorable genes of interesting, and guides for inter-ploidy gene transference from relatives into cultivated crops.